Penerapan Model Pembelajaran Jigsaw pada Pembelajaran Fisika Siswa Kelas VIII SMP Negeri 11 Lubuklinggau - Arga Dwi Muhayad; Sulistiyono; Ahmad Amin (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research aims to determine the average completeness of learning outcomes when using a learning model. The research method used in this research is an experimental research method. This type of research is Pre-Experimental research with an experimental design that will be used in the form of a One Group pre-test and post-test design. This research uses a quasi-experimental method and a quantitative descriptive approach. The population of this research was class VIII students at SMP Negeri 11 Lubuklinggau. 2024/2025 academic year. The sample for this research was students in class VIII.2 of SMP Negeri 11 Lubuklinggau. Data collection techniques were carried out using test techniques. The data analysis technique was carried out using the normality test and hypothesis test, t-test and homogeneity test. The results of this research, after applying the jigsaw learning model, can complete student learning outcomes in force and movement material for class VIII.2 students at SMP Negeri 11 Lubuklinggau, this is based on an average pretest score of 24.92 and a posttest score of 72.91. The collected test data was then analyzed using the t-test, obtaining tcount (1.62) < ttable 1.71 for a significance level of 5%. This means that ho is rejected and ha is accepted, in other words the hypothesis proposed in this research can be accepted as true, so It can be concluded that the implementation of the jigsaw learning model is on average complete in class VIII.2 students at SMP Negeri 11 Lubuklinggau.